Development of a zero-dimensional method for thermodynamic analysis and NOx calculation in the prechamber of a lean-burn gas engine. (November 2022) - Oppl, Thomas; Pirker, Gerhard; Wohlthan, Michael; Wimmer, Andreas
Significant improvements in the power density and efficiency of lean-burn large gas-engines with a prechamber and their high flexibility in meeting fluctuating power requirements illustrate the potential for using these engines in stationary power generation and in the transportation sector. Since these engines have comparatively low CO2 and NOx-emissions, they are seen as a promising solution to meet stricter emission standards. However, current combustion concepts for these engines must be enhanced to improve their performance and emission behavior; simulation methods play a major role in this process. It is critical to know and understand the fundamental processes and their relationships in the prechamber and main combustion chamber; conducting detailed analyses makes this possible. Zero-dimensional methods are suitable for these analyses. Due to their shorter calculation times, they allow extensive parameter variations to be investigated. Common methods in this area are limited to calculating performance and emission related values only in the main combustion chamber. Since a considerable share of NOx-emissions from high-performance lean-burn gas-engines arise in the prechamber, it is imperative to conduct a separate thermodynamic analysis of the prechamber and its interaction with the main combustion chamber. This paper presents a zero-dimensional method with which NOx-emissions from the prechamber can be calculated separately from the emissions of the main combustion chamber. To this end, it is necessary to conduct thermodynamic analyses of both the chambers and to consider their interaction. The measurement data for development and validation of this method is provided by tests on a single-cylinder engine with separate cylinder-pressure indication for both the chambers. Based on the results of the analyses, it can be determined to what extent each of the two systems is involved in the formation of nitrogen-oxides. With knowledge of the origin of NOx-emissions, measures may be enacted that reduce total NOx-emissions.